Emerging stock markets factbook 1999 - IFC (The World Bank, 1999)
This thirteenth annual survey of emerging stock markets, prepared by the Emerging Markets Group of the International Finance Corporation (IFC), provides essential coverage of stock market characteristics for the 45 markets covered by the IFC's three highly regarded stock market indexes--the Global, Investable, and Frontier Index series